Respuesta :
Answer:
x=-2, y=-4
Step-by-step explanation:
y=2x
x+3y=-14
In the second equation equation replace y with 2x
x+3y =-14
x +3(2x) = -14
x+6x = -14
Combine like terms
7x =-14
Divide by 7
7x/7 = -14/7
x = -2
Now we can find y
y =2x
y = 2(-2)
y = -4
Answer:
x = -2 and y = -4 and (-2, -4)
Step-by-step explanation:
Step 1: Set y to 2x in the second equation
x + 3y = -14
x + 3(2x) = -14
x + 6x = -14
Step 2: Combine like terms
x + 6x = -14
7x = -14
Step 3: Divide both sides by 7
7x / 7 = -14 / 7
x = -2
Step 4: Plug in -2 for x in the first equation
y = 2x
y = 2(-2)
y = -4
(-2, -4)
Answer: x = -2 and y = -4 and (-2, -4)